Enhancing Phonological Instruction through Digital Technology: Tools, Benefits, and Challenges - Ilmi, Vivi Nurul; Ananda, Dea Riska; Harahap, Karlina; Lubis, Yani (MUDABBIR Journal Research and Education Studies, 2025)
This study explores how digital technology is integrated into phonological instruction and its impact on teaching effectiveness and student learning outcomes. Using a literature review method, the study draws on various scholarly articles, digital sources, and reputable publications to examine the use of technological tools such as interactive software, mobile applications, and online platforms in supporting phonological awareness. The findings indicate that applications like Phonics Genius, Sound Literacy, and educational videos can enhance student engagement, accommodate diverse learning styles, and promote more personalized learning experiences. However, challenges remain, such as unequal access to technology and varying levels of teacher proficiency in using these tools effectively. This study highlights the importance of combining technological tools with traditional teaching methods to create a more inclusive and effective phonological learning environment. The findings offer practical guidance for educators seeking to maximize the role of technology in language instruction.